Extrathoracic investigation in adult patients with isolated pulmonary langerhans cell histiocytosis. Issue 1 (December 2016) - Tazi, Abdellatif; de Margerie-Mellon, Constance; Vercellino, Laetitia; Naccache, Jean; Fry, Stéphanie; Dominique, Stéphane; Jouneau, Stéphane; Lorillon, Gwenaël; Bugnet, Emmanuelle; Chiron, Raphael; Wallaert, Benoit; Valeyre, Dominique; et al.
Abstract Background An important objective on diagnosis of patients with Langerhans cell histiocytosis (LCH) is to determine the extent of disease. However, whether systematic extrathoracic investigation is needed in adult patients with clinically isolated pulmonary LCH (PLCH) has not been evaluated. Methods In this prospective, multicentre study, 54 consecutive patients with newly diagnosed clinically isolated PLCH were systematically evaluated at inclusion by bone imaging and blood laboratory testing to search for subclinical extrapulmonary LCH involvement. The patients were followed over a 2-year period. At each visit, they were asked about the presence of extrapulmonary manifestations of LCH. Results In the absence of bone symptoms, the skeletal X-ray survey results were normal for all but two patients who had a localised bone lesion consistent with possible LCH involvement, that remained unchanged over 2 years of follow-up. Whole-body bone scintigraphy did not add information to the plain radiography findings for the detection of asymptomatic bone involvement in isolated PLCH. Conversely, it showed nonspecific focal bone uptake in 18 % of the patients, mainly corresponding to post-traumatic or degenerative abnormalities unrelated to LCH. Mild leucocytosis due to neutrophilia was observed in 22 % of the patients and was not related to their smoking habits. Three patients had mild isolated lymphocytosis without haematological disease, whereas two patients had mild lymphopaenia. A mild inflammatory biological syndrome was observed in a minority of patients without infection or constitutional symptoms and was not associated with progressive disease. A substantial proportion (24.5 %) of the patients had abnormal biological liver test results, including elevated liver enzymes and/or cholestasis, which were not linked to LCH involvement in this cohort. Conclusions Obtaining a thorough history and performing comprehensive physical examination are essential for staging patients diagnosed with PLCH. In the absence of symptoms or signs suggestive of extrapulmonary LCH involvement, the systematic performing of recommended bone imaging does not appear informative. Although the observed blood laboratory abnormalities were not specifically related to LCH, performing these tests in the diagnostic workup for PLCH is useful because some of these alterations may impact patient management. Trial registration ClinicalTrials.gov: No. NCT01225601; URL:www.clinicaltrials.gov